2013
DOI: 10.1364/oe.21.002393
|View full text |Cite
|
Sign up to set email alerts
|

Metal-nanowall grating transparent electrodes: Achieving high optical transmittance at high incident angles with minimal diffraction

Abstract: A novel architecture has been employed to fabricate transparent electrodes with high conductivity and high optical transmittance at high incident angles. Soft lithography is used to fabricate polymer grating patterns onto which thin metallic films are deposited. Etching removes excess metal leaving tall walls of metal. Polymer encapsulation of the structure both protects the metal and minimizes diffraction. Transmission is dependent upon the height of the walls and encapsulation and varies from 60% to 80% for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…[ 15 ] They have also shown that this performance could additionally be improved for high angles of incident light by encapsulating the grids inside a polymer fi lm. [ 30 ] The electrical and optical performance of our grids are summarized in the R s -T plot shown in Figure 7 . We have selected some of the best-performing recently published TCEs by various fabrication techniques as well as other EHD printed electrodes and ITO as references.…”
Section: Electrical and Optical Performance Of Printed Gridsmentioning
confidence: 99%
“…[ 15 ] They have also shown that this performance could additionally be improved for high angles of incident light by encapsulating the grids inside a polymer fi lm. [ 30 ] The electrical and optical performance of our grids are summarized in the R s -T plot shown in Figure 7 . We have selected some of the best-performing recently published TCEs by various fabrication techniques as well as other EHD printed electrodes and ITO as references.…”
Section: Electrical and Optical Performance Of Printed Gridsmentioning
confidence: 99%
“…The film was etched in a reactive ion etcher (RIE) by using oxygen plasma at the RF power of 150 W, process pressure of 70 mtorr, and gas flow of 50 sccm. After the first etching of the polymer, the structures were random columnar-like, with high aspect ratios and densities 40 . A second plasma treatment with argon gas at the high RF power of 200 W and process pressure of 25 mtorr was applied to the structure to reduce the aspect ratio and density.…”
Section: Methodsmentioning
confidence: 99%
“…The TEs showed high transmission even though the incidence angle is large up to 70 deg. 49 One more advantage of the metallic grating structure is heat reflection. Most thermal radiation sources, including the solar spectrum, have significant IR which is converted to heat after absorption.…”
Section: Transparent Electrodes As Replacements For Ito and Heat Mirrorsmentioning
confidence: 99%